Mulheres negras viajantes: protagonistas de suas próprias histórias contadas através de plataformas digitais - Genésio, Denise Aparecida (Universidade Federal de São Carlos, 2023)
This research focuses on analyzing the motivations that drove black women to travel, as well as assimilating the sharing of these experiences in their social networks and online communication channels. The methodology used to collect data consisted of interviews conducted digitally, allowing a qualitative approach to the analysis of the information obtained. Three black women travelers were interviewed, and their responses were compared to identify patterns and trends related to their motivations to travel. Through this research, we seek to better understand the reasons behind the trips undertaken by black women and the meaning that these experiences have in their lives. In addition, it will examine how they share these experiences in their social networks and online channels, contributing to the promotion of diversity in tourism and inspiring other black women to explore the world. The study intends to provide valuable insights into the participation of black women in tourism, revealing their personal motivations and experiences. It is expected that the results obtained may contribute to the enrichment of knowledge about tourism and encourage greater inclusion and representation in the sector, as well as opening new perspectives for future research on the subject. Therefore, it is essential that future investigations take into account this plurality of motivations and experiences, improving knowledge about tourism and its impact on women's lives. In addition, it is necessary to promote policies and practices that promote equality and social justice in the sector.
Black women travelers: protagonists of their own stories told through digital platforms
Keywords: Mulheres Negras; Viagens; Turismo; Empoderamento Feminino; Black Women; Trips; Tourism; Female Empowerment; CIENCIAS SOCIAIS APLICADAS::TURISMO